Biofilm contamination in confined space stations: reduction, coexistence or an opportunity? - Marra, Daniele; Ferraro, Rosalia; Caserta, Sergio (Frontiers in Materials, 2024)
The prolonged human permanence in confined environments in space, such as in the case of the International Space Station, has inadvertently fostered conditions leading to uncontrolled microbial proliferation on surfaces, known as biofilm. Biofilm presence represents a challenge in critical spacecraft systems, that can lead to contamination issues and systems loss of function due to biofouling phenomena. This scenario is further complicated by microgravity that has a controversial role on biofilm growth and formation. Biocontamination can be a limiting factor in human long-term mission in outer Earth orbit and an economic and health issue on ISS.This study addresses the pressing need for effective antimicrobial strategies against such resilient biofilms in confined environments where the usage of biocidal chemical compounds is strictly controlled due to toxicity dangers. Traditional methods can be complemented by advanced antimicrobial coatings techniques. A promising approach is based on the oxygen plasma as coating platform. The technology can be potentially extended to a wide range of antibiofilm agents (e.g. peptides, bacteriophages, nanoparticles, quorum sensing disrupting agents, etc.) and substrates (e.g., metal, plastic, ceramic) showing an exceptional flexibility.An alternative vision of the biofilm challenge can be inspired by the dual nature of biofilms, addressed as "good" or "bad" depending on the specific application. Indeed, biofilm have a great potential in closed systems as small space habitat (e.g., ISS) that can be inspired by their role in "large space habitat" as planet Earth itself. The replication of such a complex biological equilibrium is an open challenge.